Long-term clinical outcomes in patients with multiple sclerosis who are initiating disease-modifying therapy with natalizumab compared with BRACETD first-line therapies - Butzkueven, Helmut; Kalincik, Tomas; Patti, Francesco; Slee, Mark; Weinstock-Guttman, Bianca; Buzzard, Katherine; Skibina, Olga; Alroughani, Raed; Prat, Alexandre; Girard, Marc; Horakova, Dana; Havrdova, Eva Kubala; et al. (Therapeutic advances in neurological disorders, 2024)
BACKGROUND: Aggressive disease control soon after multiple sclerosis (MS) diagnosis may prevent irreversible neurological damage, and therefore early initiation of a high-efficacy disease-modifying therapy (DMT) is of clinical relevance. OBJECTIVES: Evaluate long-term clinical outcomes in patients with MS who initiated treatment with either natalizumab or a BRACETD therapy (interferon beta, glatiramer acetate, teriflunomide, or dimethyl fumarate). DESIGN: This retrospective analysis utilized data from MSBase to create a matched population allowing comparison of first-line natalizumab to first-line BRACETD. METHODS: This study included patients who initiated treatment either with natalizumab or a BRACETD DMT within 1 year of MS diagnosis and continued treatment for ⩾6 months, after which patients could switch DMTs or discontinue treatment. Patients had a minimum follow-up time of ⩾60 months from initiation. A subgroup analysis compared the natalizumab group to patients in the BRACETD group who escalated therapy after 6 months. Outcomes included unadjusted annualized relapse rates (ARRs), time-to-first relapse, time-to-first confirmed disability improvement (CDI), and time-to-first confirmed disability worsening (CDW). RESULTS: After 1:1 propensity score matching, 355 BRACETD patients were matched to 355 natalizumab patients. Patients initiating natalizumab were less likely to experience a relapse over the duration of follow-up, with ARRs [95% confidence interval (CI)] of 0.080 (0.070-0.092) for natalizumab patients and 0.191 (0.178-0.205) for BRACETD patients (p < 0.0001). A Cox regression model of time-to-first relapse showed a reduced risk of relapse for natalizumab patients [hazard ratio (95% CI) of 0.52 (0.42-0.65); p < 0.001] and a more favorable time-to-first CDI. The risk of CDW was similar between groups. The subgroup analysis showed an increased relapse risk as well as a significantly higher risk of CDW for BRACETD patients. CONCLUSION: Early initiation of natalizumab produced long-term benefits in relapse outcomes in comparison with BRACETD, regardless of a subsequent escalation in therapy.